Ulica Łąkowa róg ul. Ułańskiej / fot. Karol Nowaliński. - Nowaliński, Karol (1935- ). (1987)
Przedstawia nieistniejącą dzisiaj kamienicę na rogu ul. Łąkowej i nieistniejącej dzisiaj ul. Ułańskiej, 1987 r.